1985
DOI: 10.1017/s0022112085000234
|View full text |Cite
|
Sign up to set email alerts
|

Wave generation by an oscillating surface-pressure and its application in wave-energy extraction

Abstract: A two-dimensional analysis, based on linear surface-wave theory, is developed for an oscillating-water-column wave-energy device in water of arbitrary constant depth. The immersed part of the structure is assumed of shallow draught except for a submerged vertical reflecting wall. Both the cases of linear and nonlinear power take-off are considered. The results show that air compressibility can be important in practice, and its effects may in general be satisfactorily represented by linearization. The analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
100
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(112 citation statements)
references
References 4 publications
3
100
0
1
Order By: Relevance
“…Earlier theoretical work on the hydrodynamic performance of OWCs has shown that OWC devices could have a high primary wave energy conversion efficiency if the optimized damping can be attained (Sarmento and Falcao, 6 Evans, 7 and Evans and Porter 8 ) for those fixed or simple OWC devices. For the more complicated and practical OWC devices, the boundary element method (BEM) (and the relevant commercial software, such as WAMIT [WAMIT, User Manual, www.wamit.com/manual.htm (accessed on: 10/05/2014)], ANSYS AQWA [AQWA User Manual, www.mecheng.osu.edu/documentation/Fluent14.5/145/wb_aqwa.pdf (accessed on 10/05/ 2014)], etc.)…”
mentioning
confidence: 99%
“…Earlier theoretical work on the hydrodynamic performance of OWCs has shown that OWC devices could have a high primary wave energy conversion efficiency if the optimized damping can be attained (Sarmento and Falcao, 6 Evans, 7 and Evans and Porter 8 ) for those fixed or simple OWC devices. For the more complicated and practical OWC devices, the boundary element method (BEM) (and the relevant commercial software, such as WAMIT [WAMIT, User Manual, www.wamit.com/manual.htm (accessed on: 10/05/2014)], ANSYS AQWA [AQWA User Manual, www.mecheng.osu.edu/documentation/Fluent14.5/145/wb_aqwa.pdf (accessed on 10/05/ 2014)], etc.)…”
mentioning
confidence: 99%
“…The mass flux rate of air through the turbines is proportional to the pressure difference across them. Assuming the chamber air to be compressible and its motion isentropic, then for simple harmonic motion of angular frequency u, the complex amplitudes of the total volume flux rateQ and the air pressurep a are related by [27]…”
Section: Oscillating Water Column On the Coastmentioning
confidence: 99%
“…Stated simply, the optimum energy recovery opportunity is when the OWC system is designed to have a Time Constant, T c equal to 1/6 th the wave period, T wave . The flow characteristics of the turbine along with other parameters of the OWC that define a Time Constant (T c ) are given in Equation 1. The Time Constant is a characteristic time parameter, which represents the pneumatic pressure decay within the OWC chamber.…”
Section: Sbir Backgroundmentioning
confidence: 99%